PEMANFAATAN MEDIA AJAR BERBASIS TEKNOLOGI DALAM MEMBENTUK INOVASI PEMBELAJARAN CERITA RAKYAT DI SMA - Aulia, Nurlaely; Kamiri, Kamiri (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
This research uses a qualitative approach with documentation and observation methods. Researchers observe learning activities and document the data obtained in the study. The primary data sources in this study used primary and secondary data sources. The main object in this study is the use of technology-based media. The subjects in this study were found in folklore material in high school. The results in this study lead to the use of canva-based media Features that are often used in learning are such as making power point media, Youtube learning videos in order to maximize students’ visual and listening skills, barcode scanning can be used to develop learning that is more innovative to progress, and the kahoot application has a play while learning system that supports folklore learning media in high school.